Delivering mobile library services : competency implications for vocational education and training library staff - Saravani, Sarah-Jane (Curtin University, 2013)
In a rapidly-changing technology environment, the library professional needs to demonstrate competence in the implementation of mobile technologies and resultant service delivery. The preparedness of vocational education and training sector library staff in Australasia to leverage the potential of mobile technologies has been investigated to determine the factors and relationships that influence technology acceptance. Library staff were keen to master mobile devices, believing competency to be crucial to working effectively in the mobile environment.